Impact of Ethno Religious Crisis on Library and Information Science Undergraduate Students of the University of Jos, Nigeria - Ezeala, Lily Oluebube; Olayinka, Shittu Lukman (NIU Journal of Humanities, 2020)
This study examined the impact of crisis on Library and Information Science undergraduate students in University of Jos, Nigeria. Crisis has become prevalent in many parts of the country and this is becoming wanton across Nigeria, however this study was limited to Jos North LGA because this area has been a flash point as regards issue of crisis. The objectives of the study includes; to examine the  extent to which ethno religious affects students socialization process in the University of  Jos, and to suggest ways of reducing the effects of ethno religious crisis on students among others. 3 research questions were formulated to guide the study inline with the objectives of teh study. A thorough literature review was carried out on ethno-religious crisis in various part of Nigeria. The study adopted a cross sectional survey research design and the population consisted Library and Information science undergraduate students in the University of Jos which were 376 for the academic session 2018/2019 and a sample size of 100 was randomly selected using stratified random sampling to ensure that each level provide equal ratio to the sample size. The analysis revealed that, ethno religious crisis affects students in so many ways, it affects their academic achievement, it also affects their socialization process as well as their pattern of settlement among many other effects. Another key factor causing ethno religious crisis is religion and ethnicity. The study made certain recommendations that, tolerance should be encouraged, inter faith competition should be established, religious institutions should also promote interfaith relationship among others. K eywords: Ethno Religious Crisis, Library and Information Science